Internet issues and trends : selected analyses. (Internet theory, technology and applications., 2014)
The Internet is often described as a ""network of networks"" because it is not a single physical entity, but hundreds of thousands of interconnected networks linking hundreds of millions of computers around the world. As such, the Internet is international, decentralized, and comprised of networks and infrastructure largely owned and operated by private sector entities. As the Internet grows and becomes more pervasive in all aspects of modern society, the question of how it should be governed becomes more pressing. As congressional policymakers continue to debate telecommunications reform, a m.